Epiploic Appendagitis Causing Small Bowel Obstruction: A Pleasant Surprise - Theodoros Hadjizacharias; Dionysios Dellaportas; Despoina Myoteri; Constantinos Nastos; Stavros Chaniotis; George Polymeneas (Case Reports in Surgery)
Introduction. Epiploic appendagitis is a rare cause of acute abdominal pain, mimicking acute diverticulitis or appendicitis. Epiploic appendagitis causing small bowel obstruction is highly unusual, and only a handful of such cases have been reported so far. Case Report. A 69-year-old man presented with diffuse abdominal pain and vomiting over the last 12 hours. Clinical examination, laboratory, and imaging investigations showed small bowel obstruction, and after 12 hours of conservative management, surgical exploration was decided. During surgery, a dilated terminal ileum bowel loop was found densely adhered to the sigmoid colon, attached to an inflamed epiploic appendix. The small bowel was mobilized and freed, and the inflamed epiploic appendix was resected. The postoperative course was uneventful, and the patient was discharged on the 5th postoperative day. Conclusion. Epiploic appendagitis, although a rare clinical entity, may explain small bowel obstruction symptoms.